2018
DOI: 10.1080/0284186x.2018.1484156
|View full text |Cite
|
Sign up to set email alerts
|

Development of an isotoxic decision support system integrating genetic markers of toxicity for the implantation of a rectum spacer

Abstract: This study was a proof-of-concept for an isotoxic model with genetic biomarkers with a V-IRS as a multifactorial decision support system for the decision of a placement of an IRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…[18]). Reliable NTCP models can also be used to optimize the treatment strategy [19,20]. While a meta-analysis of DVH-based NTCP models for rectal bleeding shows that there is a consensus on the parameter values based on several large studies [1], an even higher association between the dose and the risk of rectal bleeding was found when spatial features were considered [3].…”
Section: Introductionmentioning
confidence: 99%
“…[18]). Reliable NTCP models can also be used to optimize the treatment strategy [19,20]. While a meta-analysis of DVH-based NTCP models for rectal bleeding shows that there is a consensus on the parameter values based on several large studies [1], an even higher association between the dose and the risk of rectal bleeding was found when spatial features were considered [3].…”
Section: Introductionmentioning
confidence: 99%
“…Short-term future work includes merging this DSS with previously developed DSSs, including one where the effectiveness of an implantable rectum spacer is accessed on the patient level [ 37 , 38 ] as well as a DSS that compares photon to proton therapy. We also plan to expand the NTCP models by including single nucleotide polymorphisms and tumor somatic mutations to incorporate genetic information into the decision-making process [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nguyen et al (2009)[50] suggested 15 different combinations of treatment options, and this did not include the use of rectal displacement devices [65, 66] or proton therapy. The treatment mDSS that were found by the current study primarily involved RT, including treatment plan selection [46], proton compared to photon therapy [49], SBRT compared to IMRT [43], and the use of an implantable rectum spacer in EBRT [47]. Nguyen et al (2009) attempted to create a general overview of prediction tools to create a clear overview for patients, and they found most prediction tools to be focused on RT and radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%